Penyuluhan Tentang Imunisasi Tetanus Toxoid (TT) Pada Ibu Hamil Di Desa Siuhom Kecamatan Angkola Barat - Lubis, Mutia Sari; pane, mustika dewi; Batubara, Rini Amalia (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
Tetanus toxoid immunization is a process to build immunity as an effort to prevent tetanus infection. Immunization during pregnancy is very important to do to prevent diseases that can cause maternal and fetal death, the type of disposal given is Tetanus Toxoid (TT) which can prevent Tetanus disease. The purpose of this PKM is to provide information and increase the knowledge of pregnant women about the importance of carrying out Tetanus Toxoid Immunization (TT). This PKM activity was carried out using the health education method using leaflets for pregnant women as many as 6 people in Siuhom Village, Angkola Barat District. The results of this counseling activity are followed by providing an evaluation to pregnant women, namely questions and answers about the material that consumes tetanus poison (TT). Pregnant women can answer and explain well the questions posed by the instructor/speaker. The PKM activities that were carried out went well and the pregnant women who took part in the activities looked enthusiastic in participating in the activities.